2021
DOI: 10.3390/plants10030549
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Photon Spectrum on Growth and Nutritional Attributes of Baby-Leaf Lettuce at Harvest and during Postharvest Storage

Abstract: The photon flux density (PFD) and spectrum regulate the growth, quality attributes, and postharvest physiology of leafy vegetables grown indoors. However, limited information is available on how a photon spectrum enriched with a broad range of different wavebands regulates these factors. To determine this, we grew baby-leaf lettuce ‘Rouxai’ under a PFD of 200 µmol m−2 s−1 provided by warm-white (WW; control) light-emitting diodes (LEDs) supplemented with either 30 µmol m−2 s−1 of ultraviolet-A (+UV30) or 50 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Previous works have reported that the use of either monochromatic blue or red LEDs may affect several growth parameters in broccoli sprouts, but did not produce a biomass increase [ 24 , 25 ]. Neither the supplementation of warm-white light with blue or red LEDs (50 µmol m −2 s −1 ) was effective for increasing the biomass in baby-leaf lettuce [ 26 ]. Furthermore, even the combination of red/blue light may require supplemental broad-spectral energy of 500–600 nm (red–blue–white lighting) to increase the biomass in leafy crops, as the works of Lin et al and Piovene et al [ 27 , 28 ] suggest.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have reported that the use of either monochromatic blue or red LEDs may affect several growth parameters in broccoli sprouts, but did not produce a biomass increase [ 24 , 25 ]. Neither the supplementation of warm-white light with blue or red LEDs (50 µmol m −2 s −1 ) was effective for increasing the biomass in baby-leaf lettuce [ 26 ]. Furthermore, even the combination of red/blue light may require supplemental broad-spectral energy of 500–600 nm (red–blue–white lighting) to increase the biomass in leafy crops, as the works of Lin et al and Piovene et al [ 27 , 28 ] suggest.…”
Section: Resultsmentioning
confidence: 99%
“…CEAs offer many advantages for urbanized food systems. CEAs can increase plant production by environmentally controlling conditions regardless of the season [86]. One of the opportunities that indoor farming offers is optimal environmental settings by eliminating exposure to extremes in temperature, wind, and water, which can positively influence plant growth [87].…”
Section: Advantages Of Growing Crops In a Controlled Environment In U...mentioning
confidence: 99%
“…This nitrate assimilation is directly related to the optimum growth parameters and chlorophyll content of both varieties. Vaštakaitè-Kairienè et al [78] studied the characteristics of babyleaf lettuce growth under 200 µmol m −2 s −1 of warm white lights and supplemented with 30 µmol m −2 s −1 UV-A or 50 µmol m −2 s −1 blue, 50 µmol m −2 s −1 green, 50 µmol m −2 s −1 red, or 50 µmol m −2 s −1 warm white LEDs. The obtained results showed that the different supplementations did not affect the physiological development, whereas green LEDs increased the total antioxidant activity (measured by DPPH), blue LEDs increased the accumulation of secondary metabolites at harvest, and red LEDs preserved the phytochemicals during a short postharvest storage.…”
Section: Preharvest Uv and Visible Spectrum Illumination Strategies T...mentioning
confidence: 99%